Fabrication of magnetic force microscopy tips by electrodeposition and focused ion beam milling - COEY, JOHN MICHAEL DAVID (IEEE, 2008)
A method is described for the fabrication of magnetic force microscopy tips via localized electrodeposition and focused ion beam milling departing from commercial tapping mode tips. Very high aspect ratios and interacting magnetic moments are possible without altering significantly the tapping resonant frequency of the cantilever. These tips can achieve high magnetic resolution at room temperature and open atmosphere. They can also be fabricated into any shape, with applications for ferromagnetic resonance measurements and nano-imprinting.
PUBLISHED
Keywords: Terms Electrodeposition, focused ion beam milling, magnetic force microscopy (MFM), tip fabrication.